Psychometric evaluation of the Chinese version of the resilience scale for parents of children with cancer - Zhong, Gaoxiang; Ding, Zhangyi; Li, Xichen; Qiao, Yan; Zhang, Xinmiao; Cui, Huixia (Frontiers in Psychology, 2024)
Background: Pediatric cancer ranks among the leading causes of mortality in children globally.While serving as primary caregivers, certain parents may experience anxiety, depression, and other related challenges. However, not all parents succumb to such psychological distress. Resilience emerges as a potential protective factor. Assessing parental resilience holds paramount importance for healthcare professionals in identifying issues and offering tailored interventions. Yet, mainland China lacks adequate tools for this assessment. Hence, this study endeavors to translate the Resilience Scale for Parents of Children with Cancer (RSP-CC) into Chinese and scrutinize its psychometric properties.Methods: From April 2023 to January 2024, a methodological study was conducted in Chengdu, Chongqing, and Jinzhou, China, recruiting 377 eligible parents via convenience sampling for a multicenter cross-sectional survey. The translation process of the RSP-CC adhered rigorously to the Brislin model, involving forward and back-translation, followed by necessary modifications. Item analysis was assessed using the critical ratio and the item-total correlation coefficient. Validity evaluation encompassed content and internal validity assessments. Scale reliability was determined through Cronbach's α coefficient, retest reliability, and split-half reliability coefficients.The Chinese version of the RSP-CC comprises 4 dimensions and 24 items, explaining a cumulative variance contribution of 63.58%. In this investigation, the content validity index attained a score of 0.97. Exploratory factor analysis (EFA) yielded four factors consistent with the original scale, while confirmatory factor analysis (CFA) indicated satisfactory fit indices. Both Cronbach's α coefficient and retest reliability stood at 0.95, with a split-half reliability coefficient of 0.82.After rigorous translation and verification, the RSP-CC was adapted in China, demonstrating favorable psychometric characteristics. It stands as an effective instrument for parents of children diagnosed with cancer in China. Additionally, this scale could serve as a crucial tool for clinical staff in formulating specific interventions.